Gravitational Telescope - Alexander V. Lukanenkov (New Insights into Physical Science Vol. 12, 2021)
Global seismic antenna (GSA) allows detecting deformations of the Earth of a special type, characteristic of gravitational waves. GSA elements - the arbitrary ” quiet” seismic stations, aperture of GSA must be of the order 10.000 km. Pulsars are a natural source of periodic gravitational waves (GW-waves). The deformations of the Earth were detected by GSA, their amplitude \(≈\)2.5.10-15m. It was found that these deformation (strain) of the order h\(≈\)10-21. The false alarm of detecting is almost zero, equivalent to a significance of 12.8 sigma. Pulsar J0945-4833 is the most suitable source of detected deformations of the Earth.